Kesadaran Hukum sebagai Fondasi dalam Membentuk Karakter Warga Negara yang Baik - Izza Madani; Irwan Putra; Maimun Maimun; Putra Setiawan (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Legal awareness is a crucial element in shaping good citizen character, particularly in Indonesia. However, challenges in law enforcement and corruption continue to hinder public compliance with the law. This study aims to explore the relationship between legal awareness and citizen character through a qualitative literature review. Content analysis techniques were used to examine nine key articles discussing legal awareness and its implications. The results indicate that although public understanding of the law is relatively high, compliance with it remains low. Civic education and legal counseling are identified as important tools for increasing legal awareness, with a focus on teaching rights, obligations, and moral values. Furthermore, media and culture also contribute to shaping public legal behavior. This study concludes that synergy between early legal education and consistent law enforcement is essential to encourage legal compliance, thereby creating law-abiding citizens. Keywords: Legal Awareness, Character, Good Citizen